Pengembangan Usaha UKM melalui Pelatihan Digitalisasi Akuntansi di Kecamatan Sumbang Kabupaten Banyumas - Winda Dwi Yanthi; Prasetya Lazuardi (Jurnal Pengabdian Bisnis dan Akuntansi, 2025)
In the current digital era, the utilization of information technology has become an essential requirement for small and medium enterprises (SMEs) to maintain business sustainability and competitiveness. SMEs in Sumbang District, Banyumas Regency, still face financial management problems, particularly related to manual bookkeeping, limited accounting knowledge, and low adoption of digital accounting systems. This community service activity aims to develop SME businesses through digital accounting training to improve financial management quality and support better decision making. The methods used include needs analysis, socialization, training on simple digital accounting applications, mentoring, and evaluation. The results show an improvement in SMEs’ understanding and skills in recording transactions, preparing simple financial statements, and utilizing financial information for business development. This activity contributes positively to strengthening financial governance and digital readiness of SMEs.